Detection and estimation of reflectivity gradients in the radar resolution volume using multiparameter radar measurements - Chandrasekar, V., author; Gorgucci, E., author; Scarchilli, G., author; IEEE, publisher (Colorado State University. Libraries, 1999)
Multiparameter radar measurements of rainfall, namely, reflectivity factor ZH, differential reflectivity ZDR, and specific differential phase KDP lie in a constrained three dimensional (3-D) space and therefore measurement of ZH, ZDR, or KDP should be consistent with the other two. This self-consistency relationship between ZH, ZDR, and KDP is valid when the radar resolution volume is homogeneous. When there are reflectivity gradients within the radar resolution cell, the self-consistency relation is perturbed. This perturbation can be utilized to detect the presence of gradients in the radar resolution volume. This paper presents a technique to detect and estimate reflectivity gradients in the resolution cell. The technique is evaluated using theoretical analysis as well as experimental data collected by the NCAR CP-2 radar. It is demonstrated that the presence of reflectivity gradients larger than a few decibels can be detected using the algorithm developed in this paper.
Keywords: polarimetry; radar resolution; precipitation; multiparameter